Reaction rate experiments with the rural secondary school teacher in mind a seminar paper - Baquiran, Carmen C. 1925- (1967)
This seminar paper discusses the comparative study of four simple experiments that can be used in secondary school chemistry to demonstrate the factors that affect reaction rates. Each experiment utilizes quantitative technique with the use of simple equipment and materials that are cheap and available in the household or local drugstores.
Thesis (M.A.T.Chemistry)--University of the Philippines, Diliman.
Keywords: Chemistry -- Study and teaching (Secondary).; Chemical reaction, Rate of